Sistem Informasi Pencatatan Kegiatan Patroli Anggota Kepolisian Di Polsek Pasar Kliwon Surakarta - Serlina, Anis; Pantjarani, Ari; Hastomo, Mursid Dwi (Indonesian Journal of Information Technology and Computing (IMAGING), 2024)
Polsek Pasar Kliwon is one of the government institutions responsible for upholding the law, maintaining order, and serving the community. One mandatory activity that must be carried out by police officers is patrolling. Every day, Polsek Pasar Kliwon deploys its personnel to perform these patrols, and each officer is required to report their activities according to their respective duties and schedules. The data collection for the police officers' patrol activities in Polsek Pasar Kliwon is done by recording them on daily activity sheets, which are then summarized by administrative personnel. However, this process has led to several issues, including inaccuracies in activity records, delays in data processing and activity analysis, as well as vulnerability of the activity sheets to damage and loss. The objective of this research is to develop an information system for the patrol activities of police officers in Polsek Pasar Kliwon Surakarta. The author adopts the SDLC (System Development Life Cycle) waterfall model for the information system development process, utilizing PHP and MySQL programming languages. The designed information system is web-based, enabling real-time access to data for users. The intended purpose of this information system is to assist the administrative department in managing the data of police officers' patrol activities in Polsek Pasar Kliwon Surakarta.